2005
DOI: 10.1055/s-2005-922484
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer Testing in Ischemic Stroke and Cerebral Sinus and Venous Thrombosis

Abstract: D-dimer measurement is commonly included in the diagnostic workup of patients with suspected acute symptomatic deep venous thrombosis and pulmonary embolism. As a haemostatic marker, it could be theoretically useful in other thromboembolic disorders, such as acute cerebrovascular events. In this review we summarize published literature on D-dimer testing in acute ischemic stroke and cerebral sinus and venous thrombosis (CSVT), discussing possible clinical diagnostic and therapeutical applications. In ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, imaging examinations still cannot determine whether fibrinolysis reaction exists in the human body. Therefore, studying thromboembolism at the molecular level and monitoring the expression levels of relevant molecules in the DVT progression have become new research hotspots (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, imaging examinations still cannot determine whether fibrinolysis reaction exists in the human body. Therefore, studying thromboembolism at the molecular level and monitoring the expression levels of relevant molecules in the DVT progression have become new research hotspots (11).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age seems to be an important independent risk factor for further cerebro- or cardiovascular events. Because there were relatively few patients in our study, its prognostic role remains somewhat uncertain and, as suggested by Squizzato et al 18 further larger studies are warranted.…”
Section: Discussionmentioning
confidence: 81%
“…14 Thus, despite being widely used in the diagnosis of atrial thrombi, TEE has a number of inherent limitations. [14][15][16][17][18] Earlier studies proposed that hemostatic biomarkers of hypercoagulability, cardiac dysfunction, and pro-thrombotic systemic inflammation may be useful in identifying patients at highest thromboembolic risk.. [19][20][21][22][23][24][25] In fact, thrombus formation in the cardiac chambers is mainly due to blood stasis, leading to a fibrin-rich clot very similar to venous thrombi. [26][27][28] Considering the mechanism of clot formation, it is clear that patients with AF/flutter may have increased levels of D-dimer 21,29 and up-regulated biomarkers of pro-thrombotic endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Hemostatic characteristics in relation to the D-dimer assay hypercoagulability, indices of thrombogenesis, and systemic inflammation would be useful in identifying patients with high thromboembolic risk. There is substantial evidence that in addition to the elevated D-dimer, pro-thrombotic proteins and gene-expressed immune-inflammatory biomarkers (CRP, TNF-a, IL-1b, IL-6) are associated with duration of AF, 20,21 LAA dysfunction,19 presence of atrial thrombus,20,33,38 and diagnosis of cardioembolic stroke [22][23][24][25]. In this construct, it is clear that patients with AF have increased levels of D-dimer,21,29 platelet activation, systemic inflammation,30,31 and leukocyte adhesion, which is consistent with the amplified predisposition to thrombus formation and endothelial dysfunction 32.…”
mentioning
confidence: 99%